Reciprocal Dumping with Bertrand Competition - Richard Friberg; Mattias Ganslandt (The Research Institute of Industrial Economics (IUI), 2005)
This paper examines if international trade can reduce total welfare in an international oligopoly with differentiated goods. We show that welfare is a U-shaped function in the transport cost as long as trade occurs in equilibrium. With a Cournot duopoly trade can reduce welfare compared to autarchy for any degree of product differentiation. Under Bertrand competition we show that trade may reduce welfare compared to autarchy, if firms produce sufficiently close substitutes and the autarchy equilibrium is sufficiently competitive. Otherwise it can not.
Keywords: F12; F15; L13; 330; Reciprocal Dumping; Intra-Industry Trade; Oligopoly; Product Differentiation; Transport Costs; Intraindustrieller Handel; Transportkosten; Produktdifferenzierung; Oligopol; Dumping